Opportunities for development of dynamic web interfaces in an information system for research projects - Milev Plamen (SHS Web of Conferences, 2021)
The article examines issues, related to the development of software solutions for project management. In this sense, the paper presents features of an information system for research projects. The realization of a dynamism of some of the user interfaces is a relevant issue for these software solutions. The main purpose of the article is to explore the opportunities for realization of such behavior and to present the relevant models for development of dynamic web interfaces in the information system through server-side implementation. To achieve its goal, the article uses various scientific methods, including study, analysis, research, modeling and experimentation. The results support the main hypothesis of the study, namely defining the benefits of development of dynamic web interfaces using server-side implementation. The conclusion highlights the opportunities for improvement of user experience in the information systems in the subject area through the application of the researched approach.